Description of Blood Lead Levels with Uric Acid Concentration Regarding Smoking and Period Time Habits of Exposure Batik Industry Workers - Elisa, Dela Shalsha; Permatasari, Fadila Dian; Permatasari, Octavia Sella Dwi; Harningsih, Tri (Indonesian Journal of Global Health Research, 2024)
The use of heavy metals as a mixture in the batik production process is still ongoing today. Increased concentrations of heavy metals cause accumulation in workers' bodies. Lead exposure and poisoning has now become a global concern in the environmental field. Environmental and behavioral factors, especially in terms of smoking habits, are supported by the length of time exposure to pollutants each day. Blood lead levels are a risk factor for gout. This research was conducted with the aim of providing an overview of lead levels and uric acid levels in workers at the Batik Home Industry in Banaran Village based on smoking habits and length of time exposure to pollutants each day. The examination was carried out at the Yogyakarta City Health and Calibration Laboratory Center (BLKK). The research method used was descriptive of workers blood samples. The sampling technique used was purposive sampling. Samples are selected based on predetermined criteria. Samples were analyzed using an Atomic Absorption Spectrophotometer. The results of research on 24 respondents showed that the lowest lead level was 0,030 μg/dL and the highest was 4,896 μg/dL. The lowest range of uric acid levels is 4,0 mg/dL and the highest is 11,8 mg/dL. The average period of time that workers are exposed to pollutants is 8 hours/day and there are 11 respondents who have a smoking habit. Based on these results, it is stated that every worker has lead levels in their blood but it does not cause toxic effects.